Transfer factors and bioaccumulation of some heavy metals in muscle of a freshwater fish species: A human health concern - Canpolat, Özgür; Ero?lu, Mücahit; Çoban, Mehmet Zülfü; Düşükcan, Mustafa (Parlar Scientific Publications, 2014)
In this study, some heavy metal concentrations (Fe, Zn, Cu, Cd, Co, Cr, Pb, As, Hg and Ni) were determined in water and in muscle of Aspius vorax to study to potential human risk of consumption, and the relationship between the heavy metal load of fish and some of their biological aspects (weight, length and sex). In addition, transfer factors of heavy metals in A. vorax were determined. It was found that heavy metals accumulated in muscle of A. vorax in concentrations higher than that in water. The orders, in relation to the heavy metal levels in muscle and water, were found to be Fe>Zn>Cu and Zn> Fe>Cu. The results were discussed and compared with tolerable values for heavy metals provided from EPA and FAO to determine whether this species has any risk for human consumption. © by PSP.
Keywords: Aspius vorax; Heavy metals; Human consumption; Transfer factor; Turkey